Critical Role of Extracellular Vesicles in Diffuse Large B-Cell Lymphoma; Pathogenesis, Potential Biomarkers, and Targeted Therapy—A Narrative Review - Teerachat Punnachet; Siriporn C. Chattipakorn; Nipon Chattipakorn; Sirinart Kumfu (Biomedicines)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin’s lymphoma, characterized by its aggressive nature and heterogeneity. Despite significant advances in understanding DLBCL pathogenesis, there is still a need to elucidate the intricate mechanisms involved in disease progression and identify novel therapeutic targets. Extracellular vesicles (EVs), including exosomes and microvesicles, have emerged as crucial mediators of intercellular communication in various physiological and pathological processes, including cancer. In recent years, evidence has suggested that EVs play a vital role in DLBCL biology by facilitating the exchange of genetic material, especially miRNAs, and proteins and lipids between tumor cells, immune cells, and the tumor microenvironment. We summarize and discuss the biological functions of EVs in DLBCL and their effects on the tumor microenvironment, highlighting their influence on DLBCL pathobiology, immune evasion, angiogenesis, and drug resistance. We also investigated EVs’ diagnostic and prognostic potential as circulating biomarkers in DLBCL, emphasizing their utility in the non-invasive monitoring of the disease status and treatment response. Understanding the complex interplay between EVs and DLBCL may open up new avenues for personalized medicine, improve patient stratification, and facilitate the development of innovative therapeutic interventions in this devastating hematological malignancy.